Clinical and Epidemiological Features of Pediatric Patients with COVID-19 in a Tertiary Pediatric Hospital - De Filippo, Maria; Magri, Paola; Bossi, Grazia; Brambilla, Ilaria; Castagnoli, Riccardo; Mascolo, Amelia; Votto, Martina; Licari, Amelia; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2022)
Background: Coronavirus disease 2019 (COVID-19) affects people of any age with high mortality and morbidity in adults older than 65 years. Reports on pediatric cases highlighted those children generally develop milder symptoms than adults or are asymptomatic. We aimed to assess the epidemiological and clinical data of children and adolescents with SARS-CoV-2 infection to improve pediatric COVID-19. Methods: We retrospectively analyzed clinical and epidemiological features of patients with SARS-CoV-2 infection hospitalized at the Pediatric Hospital of Pavia, Italy, between February 1, 2020, to April 30, 2021. Results: 71 patients aged 0-16 years were included; 33 (46%) females and 38 (54 %) males. Thirty-three (46%) patients had comorbidities, such as obesity and hematological diseases. Thirty-one children (44%) were exposed to COVID-19-positive household members. Nine (12.7 %) patients were asymptomatic, whereas 57 (80.3%) had a mild-moderate disease. Only five (7%) showed a severe or critical disease, and two patients required ICU admission. The most frequent symptoms were fever (76%), loss of appetite (26%), gastrointestinal symptoms (19%), and cough (19%). Chest X-ray was performed in 42 patients showing lung abnormalities in more than half of symptomatic patients. The most common laboratory features were lymphopenia and eosinopenia associated with high levels of inflammation markers. Conclusions: This study confirmed that COVID-19 has a mild course in children compared to adults. Most of the enrolled children were asymptomatic or had a mild-moderate disease. Patients with comorbidities were more prone to develop clinical complications.